BS EN 63232-1-2. Live working. Hand protective devices against the thermal hazards of an electric arc. Part 1-2. Test methods. Method 2. Determination of arc protection class of hand protective devices by using a constrained and directed arc (box test) (6th September 2021) - British Standards Institution
No abstract available